On zeros of the derivative of the Lerch zeta-function - Ramūnas Garunkštis (Lietuvos Matematikos Rinkinys)
We consider zeros of the derivative of the Lerch zeta-function. We obtain some lower bound for the number of zeros lying on the right from the critical line.